STRENGTHENING HUMAN RELATIONS IN THE ORGANIZATION BASED ON SARANIYADHAMMA VI OF SCHOOLS IN THUGYAI CONSORTIUM UNDER THE SECONDARY EDUCATIONAL SERVICE AREA OFFICE NAKHON SI THAMMARAT - Jansrinual, Saifon; PhrakhruKhemathammakhosit; Wiraponkan, Boonlert (Journal of Educational Review Faculty of Education in MCU, 2025)
This research article aimed to: 1) Study the state of human relations in the organizations of schools in Thungyai Consortium, 2) Explore the ways to enhance human relations in the organization based on the principles of Six Sraṇiyadhamma of schools in Thungyai Consortium, and 3) Present and evaluate the approach for enhancing human relations in the organization based on the Six Sraṇiyadhamma of schools in Thungyai Consortium. This is a qualitative research study, with data collected through in-depth interviews with 15 stakeholders, 5 experts, and 7 group discussion participants. Qualitative data were analyzed using content analysis. The research findings revealed that: 1) The state of enhancing human relations in the organization was not yet systematic, with unclear communication and a lack of continuity in collaboration. Personnel did not share or listen to each other’s opinions, and physical and mental environment was not as conducive as it should be. Therefore, enhancing human relations in the organization required careful planning and continuous implementation for sustainable development. 2) The approach to enhancing human relations in the organization, according to the Six Sraṇiyadhamma principles of the schools in Thungyai Consortium, consisted of 1. Understanding oneself, 2. Understanding others, and 3. Understanding the environment, in accordance with the Six Sraṇiyadhamma principles. The implementation steps included knowledge creation planning, organizing activities to enhance human relations in the organization, and monitoring and evaluating the results. 3) In presenting and evaluating the approach to enhancing human relations in the organization based on the Six Sraṇiyadhamma principles, it was found that this was appropriate, feasible and useful for use in enhancing human relations in organizations.